2017
DOI: 10.3389/fphar.2017.00364
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Resistance: Influencing Factors

Abstract: Rational use of antibiotic is the key approach to improve the antibiotic performance and tackling of the antimicrobial resistance. The efficacy of antimicrobials are influenced by many factors: (1) bacterial status (susceptibility and resistance, tolerance, persistence, biofilm) and inoculum size; (2) antimicrobial concentrations [mutant selection window (MSW) and sub-inhibitory concentration]; (3) host factors (serum effect and impact on gut micro-biota). Additional understandings regarding the linkage betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 113 publications
5
97
1
8
Order By: Relevance
“…As already cited, among those metabolites are formic acid, free fatty acids, ammonia, ethanol, hydrogen peroxide, diacetyl, acetoin, 2,3-butanediol, acetaldehyde, benzoate, bacteriolytic enzymes, bacteriocins and BLIS, as well as several other less known inhibitory substances [1,3,4,10,41,[58][59][60][61][62][63][64]. Furthermore, the antimicrobial effect of LAB can also be significantly influenced by numerous physical, chemical and nutritional environmental factors [65,66].…”
Section: Antimicrobial Activity Of the Isolated Lactic Acid Bacteriamentioning
confidence: 99%
“…As already cited, among those metabolites are formic acid, free fatty acids, ammonia, ethanol, hydrogen peroxide, diacetyl, acetoin, 2,3-butanediol, acetaldehyde, benzoate, bacteriolytic enzymes, bacteriocins and BLIS, as well as several other less known inhibitory substances [1,3,4,10,41,[58][59][60][61][62][63][64]. Furthermore, the antimicrobial effect of LAB can also be significantly influenced by numerous physical, chemical and nutritional environmental factors [65,66].…”
Section: Antimicrobial Activity Of the Isolated Lactic Acid Bacteriamentioning
confidence: 99%
“…These guidelines recommend AST using cation adjusted Mueller-Hinton broth (CAMHB) as growth medium and define a bacterial inoculum of ∼5 × 10 5 CFU/mL (Clinical andLaboratory Standards Institute, 1999, 2015). However, the susceptibility of bacteria to antibiotics are influenced by many factors such as bacterial inoculum size, composition of the medium (e.g., pH, ion concentrations) and host factors (e.g., serum factors) (Yang et al, 2014;Li et al, 2017). A recent study showed an increase of colistin Minimal inhibitory concentration (MIC) values for colistin-resistant strains by enhancing the calcium concentration in CAMHB (Gwozdzinski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This was particularly important because antibiotic exposure for FTIR measurements was conducted at a cell density three orders of magnitude higher than MIC testing, which was required to obtain sufficient biomass for spectra acquisition. Although the relationship between inoculum size and antimicrobial activity is not linear [33,34], previous studies have shown that four times the MIC is a suitable concentration for metabolomics analysis of antibiotics MOA [23]. Moreover, determining the average inactivation also attested that using a relative antibiotic concentration, e.g., four times the MIC, over an absolute concentration, e.g., 500 ug/mL, resulted in an equivalent antibiotic effect (i.e., equivalent inactivation) between different metabolic fingerprints.…”
Section: Minimum Inhibitory Concentrations (Mics) and Bacterial Inactmentioning
confidence: 99%